Analisis Faktor Yang Berpengaruh Terhadap Minat Berwirausaha Pada Mahasiswa STMIK STIKOM Indonesia - Desmayani, Ni Made Mila Rosa (JIMAT (Jurnal Ilmiah Mahasiswa Akuntansi) Undiksha, 2021)
The purpose of this study was to determine the analysis of factors that influence the interest in entrepreneurship in STMIK STIKOM Indonesian students. Described using attitude factors and contextual factors. The data collection method in this study used a questionnaire technique. The population of this research is STMIK STIKOM Indonesia students. The sample used is purposive sampling method, with the number of respondents 92 students by spreading using google form. The data analysis technique used was multiple linear regression. Based on the test results, the results of the research instrument test & classical assumption test show that all variables are declared reliable & valid and meet the classical assumption test. The results of hypothesis testing indicate that attitude factors and contextual factors have a positive effect on the entrepreneurial interest of STMIK STIKOM Indonesian students.